Continued professional development practices in Malaysian service-based industry / Fadilah Puteh, Maniam Kaliannan and Nafis Alam - Puteh, Fadilah; Kaliannan, Maniam; Alam, Nafis (Research Management Institute (RMI), 2014)
The concept of Continued Professional Development (CPD) through continuous learning calls upon organisations to encourage, support, and provide favourable environment for employees to engage in continuous learning. This will help to avoid ‘professional obsolete syndrome’; a syndrome faced by a majority if not all employees. This study intends to investigate the current practices of CPD in the Malaysian service-based industry. This article presents the results of an analysis of CPD practices using a qualitative approach based on several interviews with subjectmatter- experts from various sectors in the Malaysian service-based industry. Fifteen HR Directors and HR Managers were interviewed in order to gauge their perspectives on the current practices of CPD as this will depict the actual scenario on how they see; interpret; regulate; implement; and enforce CPD for staffs’ development. The data which was collected via interviews was transcribed and analyzed using thematic analysis. The findings revealed different approaches or practices of CPD among several service sectors in Malaysia.